Workshop Eco Maggot : Studi Kasus Dampak Sosialisasi Pelaksanaan Zero Food Waste Di SD Laboratorium UPI Purwakarta - Erna Suwangsih; Anggi Rahma; Ighna Zahra Habibina; Kartika Sari; Putri Ayu; Rachma Nurfitria; Tiominar Febrianti Puspitasari; Ummyatul Salsabhila; Wilda Nur Laila (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The Eco Maggot Workshop at SD Laboratorium UPI Purwakarta aimed to raise awareness among teachers and parents about the importance of managing food waste through the promotion of zero food waste practices and the introduction of Black Soldier Fly (BSF) maggots as a solution for handling organic waste. This workshop was designed to enhance participants' understanding of the environmental impact of food waste and to offer innovative solutions for its management. The study employed a qualitative approach with a case study research method, where data was collected through observation and interviews with workshop participants. The findings revealed that participants experienced increased awareness and motivation to implement zero food waste practices both in their schools and households. The use of maggots as an organic waste management solution was also perceived as effective by the participants.